2007
DOI: 10.4161/cc.6.9.4218
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Endonuclease G Selectively Kills Polyploid Cells

Abstract: Endonuclease G is a mitochondrio-nuclear located nuclease with dual-vital and lethal-functions. Besides its role in apoptosis execution, we have recently shown that depletion of endonuclease G leads to necrotic cell death in yeast. Here, we present further mechanistic elucidation of endonuclease G's vital functions. The deletion of the yeast Endonuclease G gene causes the complete elimination of tetraploid cells during exponential growth. Consistently, conditional knockdown of mammalian endonuclease G selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…5 In fact, a vital role of EndoG in the maintenance of polyploid cells has been recently described for both yeast cells and human cancer cells. 78 In humans, mitochondrial fragmentation (fission) plays a causal role in apoptosis and is regulated by the dynaminrelated protein-1 (Drp1). Mitochondrial shape transitions are critical for yeast cell death, as well: for instance, upon challenge with diverse death stimuli, the yeast homolog of Drp1 (Dnm1p) promotes apoptosis preceded by mitochondrial fragmentation and degradation.…”
Section: Proteins and Pathways Regulating Yeast Apoptosismentioning
confidence: 99%
“…5 In fact, a vital role of EndoG in the maintenance of polyploid cells has been recently described for both yeast cells and human cancer cells. 78 In humans, mitochondrial fragmentation (fission) plays a causal role in apoptosis and is regulated by the dynaminrelated protein-1 (Drp1). Mitochondrial shape transitions are critical for yeast cell death, as well: for instance, upon challenge with diverse death stimuli, the yeast homolog of Drp1 (Dnm1p) promotes apoptosis preceded by mitochondrial fragmentation and degradation.…”
Section: Proteins and Pathways Regulating Yeast Apoptosismentioning
confidence: 99%
“…Interestingly, it has been demonstrated that EndoG is required for the survival of tetraploid S. cerevisiae cells, an observation that was confirmed in tetraploid human colon cancer cell clones. 87 Finally, metacaspases (which may represent a phylogenetic ancestor of mammalian caspases) are not only implicated in various cell death scenarios, 143 but have been recently shown to modulate cell cycle progression and stress responses in fungal and protozoan models. 144,145 …”
Section: Day Jobs Of Night Killers L Galluzzi Et Almentioning
confidence: 99%
“…85 In accord with the observation that recombination-dependent DNA repair is essential for the survival of tetraploid cells, 86 EndoG knockdown causes the death of tetraploid tumor cells. 87 The stress-activated endoprotease Omi stress-regulated endoprotease (Omi) (also known as high temperature requirement protein A 2, i.e. HtrA2) belongs to a family of serine proteases that is well conserved from bacteria to humans.…”
Section: Vital Functions Of Mitochondrial Death Effectorsmentioning
confidence: 99%
“…EndoG is also thought to function in a non-apoptotic form of programmed cell death (21). Evidence for a positive function of EndoG in cell proliferation has been presented (8,22,23). A proposed role of mammalian EndoG in the genomic inversion of herpesvirus (22,24) suggests the possibility that not all of EndoG is sequestered in mitochondria.…”
mentioning
confidence: 99%